PENGEMBANGAN POTENSI DESA HENDROSARI SEBAGAI DESA WISATA EDUKASI DI KABUPATEN GRESIK - Diana Hertati; Dinda Fitri Ayu Rahmawati; Qoric Arsita; Silvia Eka Ramadhani Putri Gunawan (Universitas Halu Oleo, 2021)
This study aims to determine how the development carried out to realize the concept of education in Lontar Sewu Tourism Education through its potential and can improve the economy and make Hendrosari Village better known by the outside community with a good image. The method in this research is descriptive qualitative and uses the theory of developing the potential of a tourism village.The results of the research carried out require a development based on the potential of Hendrosari Village, namely when viewed from the natural tourist attraction which is used as a tourist village because it has a large area of land planted with palm trees and the community fully contributes to building the village. In the aspect of attractions, the use of nature as a vehicle for attractions has been carried out in accordance with the development of tourist destinations, but in its implementation there is no concept of education in accordance with the purpose of establishing the Lontar Sewu Tourism Edu. Supporting facilities in the Edu Wisata Lontar Sewu area are adequate, then from the aspect of transportation accessibility it can only be passed by using a private vehicle with the road conditions to Edu Wisata Lontar Sewu not good because there are many potholes and bumpy roads that make motorists feel uncomfortable and have to be careful. heart when passing through the road, because there is only one entrance to the destination.